Dosimetric Characteristics of Aqueous Solutions of Sandalfix Red Dye for Gamma Dosimetry - Taqmeem Hussain; Muhammad Shahbaz; Inam-ul-Haq; Hashim Farooq; Nasir Amin; Yasir Jamil (Journal of Basic & Applied Sciences, 2021)
Gamma dosimetric behavior of the aqueous solutions of the Sandalfix Red (C.I. Reactive Red 195A) dye was studied. The sample solutions of two chemical natures i.e., Acidic and Alkaline; were irradiated by Co60 ?-source in the range 0-100kGy. The "Control samples" were kept un-irradiated and also chemically neutral. The dosimetry was done in three phases i.e., Low, Intermediate and High, ranging from 100-1000Gy, 1-10kGy and 10-100kGy respectively. The found values of the "λmax" and the molar extinction coefficient "ε" of the dye were 565nm and 0.19×104 dm3 mol-1cm-1 respectively. The absorbance (A) of the aqueous solutions was studied at the absorption band maxima (λmax). It was hence found that the aqueous solutions of the Sandalfix Red C4BLN dye were able to be used as passive dosimeters in the range 10-100 kGy i.e., the sample solutions have shown radioactive exponential behavior of response in the "Intermediate and High dosimetry". However, a linear response was shown by the sample solutions in the "Low dosimetry".